Performance of high-belite calcium sulfoaluminate cement subjected to hydrochloric acid and sulfuric acid - Huo, Guang; Jiang, Xinchao; Sun, Xiaoheng; Li, Hui; Shi, Hongxing (Frontiers in Materials, 2024)
The high-belite calcium sulfoaluminate cement (HB-CSA) has displayed outstanding acid resistance. However, further research is needed to understand the mechanism behind its acid resistance fully. This study investigates the resistance of a new type of HB-CSA to hydrochloric and sulfuric acid. Additionally, the impact of the ye'elimite (C4A3S¯)-to-gypsum (CS¯) ratio on the acid resistance of HB-CSA is discussed. The resistance performance is investigated by flexural strength and resistance index analyses, X-ray diffraction (XRD), thermogravimetric analysis (TGA), electronic computed tomography (CT) scans, and scanning electron microscopy (SEM). The results show that the HB-CSA exhibits superior resistance to sulfuric acid and hydrochloric acid compared to Portland cement. The absence of portlandite contributes to the enhanced performance of HB-CSA. In addition, as the C4A3S¯-to-CS¯ ratio decreases, the content of Aft in HB-CSA increases, leading to an increase in the acid resistance of HB-CSA.